2020
DOI: 10.3390/su12198204
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Child Poverty and Its Uncertainty: A Case Study of 33 European Countries

Abstract: Over the last few years, there has been increased interest in compiling poverty indicators for children, as well as in providing uncertainty measures that are associated with point estimates. In this paper, we provide point, variance, and interval confidence estimates of the at-risk-of-poverty rate indicator for 33 European countries. Using the 2018 EU-SILC survey, we analysed the spatial distribution of poverty by providing graphical representations at the national level. Our results reveal rates of child pov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…However, the relationship between child poverty and the different categories of social expenditures is not similar. In all the estimated models, and in accordance with previous studies [12,20,22], we find a negative relationship between child poverty and government spending on education and health, whereas a positive correlation is found with government social protection spending. Likewise, our findings lead us to confirm our hypothesis that the correlation between child poverty and government social spending differs depending on the tax structure of the Member States.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the relationship between child poverty and the different categories of social expenditures is not similar. In all the estimated models, and in accordance with previous studies [12,20,22], we find a negative relationship between child poverty and government spending on education and health, whereas a positive correlation is found with government social protection spending. Likewise, our findings lead us to confirm our hypothesis that the correlation between child poverty and government social spending differs depending on the tax structure of the Member States.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the relationship between child poverty and the different categories of social spending is not clearly established. Considering the items of government spending in education and health, related literature has found that a higher spending in both helps to reduce child poverty rates [12,20,22]. However, the association between spending on social protection and child poverty is not well defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, a nonparametric bootstrapping approach that makes no assumptions about the nature of the underlying population is more appropriate (Chernick 1999 ). Indeed, bootstrapping is a popular method of producing confidence intervals because of its generality (see, among others, Benedetti et al 2020 ; D’Agostino et al 2022 ; Rousselet et al 2021 ). Accordingly, for comparing two groups, we create the distribution of bootstrap differences in the means (i.e., we generate M bootstrap samples from each group and compute the statistic of interest ( ) for each bootstrap sample), and then we use the 25th value and the 975th value of the ranked differences as boundaries of the 95% confidence interval.…”
Section: Methodsmentioning
confidence: 99%
“…The second dimension shows high factor loadings for items regarding expenditure for children needs and education. Therefore, we interpret it as an indicator of “Children specific deprivation” (see Carraro and Ferrone 2020 ; Benedetti et al 2020 for related studies on this topic).…”
Section: Measurement Issue and Empirical Findingsmentioning
confidence: 99%